2015
DOI: 10.1007/s12088-015-0514-z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Origin of Clostridium botulinum Strains: Evolution of Distinct Restriction Endonuclease Sites in rrs (16S rRNA gene)

Abstract: Diversity analysis of Clostridium botulinum strains is complicated by high microheterogeneity caused by the presence of 9-22 copies of rrs (16S rRNA gene). The need is to mine genetic markers to identify very closely related strains. Multiple alignments of the nucleotide sequences of the 212 rrs of 13 C. botulinum strains revealed intra- and inter-genomic heterogeneity. Low intragenomic heterogeneity in rrs was evident in strains 230613, Alaska E43, Okra, Eklund 17B, Langeland, 657, Kyoto, BKT015925, and Loch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Clostridium has a broad range of biotechnological applications, but can cause illness and deadly diseases like pneumonia, bacteremia, botulism, myonecrosis, and tetanus [21][22][23]. Clostridium are noted to contain either single or multiple QSS, such as: (1) LuxS, (2) Agr, (3) Agr2 that are regulated by peptide signals e.g., AIP ( Table 1) [24][25][26][27][28][29].…”
Section: Clostridiummentioning
confidence: 99%
“…Clostridium has a broad range of biotechnological applications, but can cause illness and deadly diseases like pneumonia, bacteremia, botulism, myonecrosis, and tetanus [21][22][23]. Clostridium are noted to contain either single or multiple QSS, such as: (1) LuxS, (2) Agr, (3) Agr2 that are regulated by peptide signals e.g., AIP ( Table 1) [24][25][26][27][28][29].…”
Section: Clostridiummentioning
confidence: 99%
“…Among the various genes based identification methods, the most widely employed has been the usage of rrs gene [12][13][14][15][16]. It has proved instrumental in bacterial identification; however, the major difficulty encountered is in the cases where the organism has multiple copies of rrs within the genome [13,14,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Although, recA is one of those genes which are used widely for identification of Streptococcus [27], however, our analysis revealed that it is not among the best candidates, which can be exploited for Table 5 continued detection of Streptococcus infections especially in the cases of S. mutans (2 strains), S. pneumoniae (20 strains), S. pyogenes (3/7 strains), and S. suis (5/9 strains) (Table 5a, b). In the similar manner, analysis of gyrB gene, commonly used as biomarker for identification in general [13], was also not very effective as the unique RE patterns could not be deduced in the following cases: S. pneumoniae (18/20 strains), S. pyogenes (4/7 strains), and S. suis (6/9 strains) (Table 6a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations